Six new species of oonopid spiders from Champasak, Laos (Araneae, Oonopidae) - Tong, Yanfeng; Li, Shuqiang (Zootaxa, 2013)
Five genera and nine species of oonopid spiders are recorded from Laos, including six new species: Gamasomorpha comosa Tong & Li, 2009, Ischnothyreus corollacous sp. nov., Ischnothyreus tadetu sp. nov., Ischnothyreus tadfane sp. nov., Opopaea cornuta Yin & Wang, 1984, Opopaea lemniscata sp. nov., Opopaea tumida sp. nov., Xestaspis loricata (L. Koch, 1873), and Xyphinus pakse sp. nov.